IJCM_97A: Clinico-epidemiological profile and outcome of Severe Acute Malnutrition children admitted to the nutritional rehabilitation centre of a tertiary care hospital in Kalaburagi, Karnataka: a retrospective study - Sreeshyam K S; Gururaj N A; Ramesh; Ajaykumar G. (Wolters Kluwer Medknow Publications, 2024)
Background: Severe acute malnutrition is the major cause for under- five morbidity and mortality. According to NFHS 5 (2019-20), 7.7% of malnourished children under 5 years in India were severely wasted and in Karnataka it is 8.4 %. There is paucity of data on risk factors and clinical outcomes related to SAM children in North Karnataka, hence the present study was conducted. Objectives: 1. To assess the clinico-epidemiological profile of SAM children. 2. To determine the risk factors of SAM children admitted in NRC. 3. To study outcomes of SAM children admitted in NRC. Methodology: Study setting: Nutritional Rehabilitation Centre of Gulbarga Institute of Medical Sciences, a Tertiary care hospital in Kalaburagi. Study design: A retrospective record- based cross-sectional study Study population: All children under 5 years of age admitted with SAM in the NRC at GIMS, Kalaburagi. Study duration: December 2022- November 2023 Sample size: As per data from Medical Records Department, total number of SAM children admitted in NRC is 180 between December 2022 to November 2023. DATA COLLECTION METHOD: In all the admitted patients, a detailed history including socio demographic, clinical presentation, birth order, immunization and duration of stay in NRC, physical examination findings and investigations were collected from available records. Anthropometric measurements like weight, length /height, MUAC and weight for height were collected and analysed using WHO growth charts. The outcomes included whether the children completed duration of stay at NRC were cured with weight gain, no weight gain or succumbed to malnutrition. Inclusion criteria: All children under 5 years who were admitted and fulfilled the criteria of SAM by WHO. Exclusion Criteria: 1. Case sheets of admitted SAM children with incomplete data. STATISTICAL ANALYSIS: Data were entered in Microsoft excel sheet and analyzed using SPSS version 20. Results: Among 150 SAM children analysed,77 (51.7%) males and 73(48.3%) females had weight for height below - 3SD. Conclusion: Hospital-based management of SAM children in NRC with adherence to updated WHO standard guidelines has helped in reducing mortality and morbidity among undernourished children.